2003
DOI: 10.1074/jbc.m305986200
|View full text |Cite
|
Sign up to set email alerts
|

Insect Cytokine Growth-blocking Peptide Triggers a Termination System of Cellular Immunity by Inducing Its Binding Protein

Abstract: Growth-blocking peptide (GBP) is a 25-amino acid cytokine found in lepidopteran insects that possesses diverse biological activities such as stimulation of immune cells (plasmatocytes), cell proliferation, and larval growth regulation. We found another novel function of GBP that induces a hemolysis of another class of blood cells (oenocytoids). In the lysate of oenocytoids we identified a GBP-binding protein that shows a specific affinity for GBP. The characterization of purified GBP-binding protein and its cD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 34 publications
1
46
0
Order By: Relevance
“…Each purified protein was emulsified by Titer Max Gold (CytRx Co.) and injected into a rabbit to generate a specific polyclonal antibody. The antibodies were precipitated by adding ammonium sulfate to 40% saturation and further purified by an affinity column of protein G-Sepharose (GE Healthcare) (20). Proteins of Drosophila larval brains were separated by SDS-PAGE and electrically transferred to a polyvinylidene difluoride membrane filter.…”
Section: Methodsmentioning
confidence: 99%
“…Each purified protein was emulsified by Titer Max Gold (CytRx Co.) and injected into a rabbit to generate a specific polyclonal antibody. The antibodies were precipitated by adding ammonium sulfate to 40% saturation and further purified by an affinity column of protein G-Sepharose (GE Healthcare) (20). Proteins of Drosophila larval brains were separated by SDS-PAGE and electrically transferred to a polyvinylidene difluoride membrane filter.…”
Section: Methodsmentioning
confidence: 99%
“…A cytokine-like molecule (coelomic cytolytic factor) found in the earthworm, Eisenia foetida, with lectinlike activities similar to TNF instead suggests a convergent evolution of cytokines (9). Similarly, the ENF peptides found in some lepidopteran insects have cytokine-like activity, but they lack any sequence homology to vertebrate proteins (10,11).…”
mentioning
confidence: 99%
“…Excessive amount of PPs cause serious damage to insect self organization. Paralytic peptide binding proteins are also up-regulated during the diapause period, which suggests that PP-BP act as active regulators of the paralytic peptide (Matsumoto et al, 2003), as even the over expression of the paralytic peptide might cause damage to the cells.…”
Section: Multigene Organization Of B Mori Pp-bp Genementioning
confidence: 98%
“…The C-terminal amino acid sequence (190th-430th amino acids) of B. mori paralytic peptide binding proteins is homologous to 30KPs (Hu et al, 2006). Growth-blocking peptide binding protein was reported to function for silencing the GBP action (Matsumoto et al, 2003) In a recent study by Zhang et al, (2012), 73 genes of Lipoprotein_11 family were retrieved from 12 lepidopteran species and the structural analysis showed that these genes could be divided into three distinct subfamilies according to their differential N-terminal domain. A novel subfamily of Lipoprotein_11 was reported for the first time in the study and named serine/threonine-rich 30KP according to its exclusive domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation